Investigating the Impact of Urbanization on Living Standards, Infrastructure and Environment: A Case Study of Six Major Cities of Punjab, Pakistan - Maria Faiq Javaid; Atif Khan Jadoon; Rimsha Ramzan; Ambreen Sarwar; Liaqat Ali Waseem; Muhammad Shahid Maqbool (Al-Qanṭara, 2023)
The present research analyzes the impact of urbanization on various dimensions of economic development, i.e. infrastructure, living standards and environment. Using data from years 2002 to 2022, 17 dimensions of selected indicators are identified to study the effects of urbanization on economic development for a panel of six cities in Punjab, Pakistan. Panel ARDL estimation technique is employed to study short-run and long-run effects of urbanization on development. The research concludes that, in the long run, urbanization has a negative and significant effect on economic development through infrastructure, living standards, and environment. However, this impact is insignificant in the short run. The research also establishes a bidirectional causality between urbanization and infrastructure and urbanization and living standards. However, the causal relationship runs from environment to urbanization. Moreover, unidirectional causality also exists from urbanization to economic development.